Comparative analysis of the short-term outcomes of total robotic and robot-assisted radical resection for colon cancer - Zheng Huichao; Che Jianlin; Tong Weidong; Li Fan; Huang Bin; Shen Haode; Qin Ju (结直肠肛门外科)
[Objectives] To compare the short-term outcomes of total robotic and robot-assisted radical resection for colon cancer. [Methods] A retrospective analysis was conducted on the clinical data of patients who underwent robotic right colon cancer or left colon cancer radical resection in the Department of General Surgery, Daping Hospital of Army Medical University (Army Medical Center) from August 2016 to december 2023. The patients were divided into a total robotic group (n=49) and a robot-assisted group (n=68) based on the surgical approach. The general information, intraoperative conditions, postoperative complications, postoperative recovery, hospitalization costs, and postoperative pathological indicators were compared between the two groups. [Results] There were no significant differences in gender, age, body mass index, American Society of Anesthesiologists classification, tumor location, or history of abdominal surgery between the two groups (P>0.05). All surgeries were successfully completed without severe intraoperative complications such as adjacent organ injury or unexpected heavy bleeding. No conversions to laparoscopy or open surgery occurred in either group. There were no significant differences in operative time or intraoperative blood loss between the two groups (P>0.05). No anastomotic leakage occurred in either group; in the total robotic group, 1 patient (2.0%) developed chylous leakage, 3 patients (6.1%) developed incision-related complications, 3 patients (6.1%) developed postoperative intestinal obstruction, and no cases of postoperative intra-abdominal bleeding were observed. Other complications occurred in 3 patients (6.1%). In the robot-assisted group, 1 patient (1.5%) developed chylous leakage, 4 patients (5.9%) developed incision-related complications, 1 patients (1.5%) developed postoperative intestinal obstruction, 1 patients (1.5%) developed postoperative intra-abdominal bleeding, and other complications occurred in 4 patients (5.9%). There were no significant differences in the first exhaust time, hospitalization costs, overall postoperative complication rate, or Clavien-Dindo classification of complications between the two groups (P>0.05). The postoperative hospital stay in the total robotic group was shorter than that in the robot-assisted group (P<0.05). There were no significant differences in tumor differentiation, T stage, N stage, TNM stage, number of lymph nodes dissected, or number of positive lymph nodes between the two groups (P>0.05). [Conclusion] Total robotic radical resection for colon cancer is safe and feasible, and can shorten the postoperative hospital stay. However, considering factors such as surgeon habits, surgical convenience, and operational difficulties, total robotic radical resection for colon cancer is still only a supplement to laparoscopic or robot-assisted surgery. Whether this procedure has advantages over traditional robot-assisted surgery and its long-term outcomes still require further verification by high-level evidence-based medical evidence in the future.